Developing Local Wisdom Content in West Kalimantan as English Language Teaching Material - Yusawinur Barella (IKIP PGRI Pontianak, 2020)
English is an international language, and almost all Indonesians are aware that most of the teaching materials that use English contain foreign cultural content and topics from abroad. This will cause students to be less aware of the culture of the nation, because they are more focused on understanding foreign cultures. This problem will be incompatible with the goals of national education, which emphasize the development of national cultural identity and the formation of virtuous character, as well as the competitiveness of human resources for the Indonesian nation. This research is the development of teaching materials that aim to produce a product that will later be useful for students in improving their English language skills. In this study also discusses how a teacher can manage their teaching from rich local materials and resources into attractive teaching and learning management.As a teaching material, the product produced is English-language material, using easy-to-understand vocabulary, and is not accompanied by practice questions at the end of the reading, so that students can read calmly.